Model Evaluasi Ekop Dalam Lembaga Pendidikan Islam - Dandun Setiawan Fambudi; Hamdan Junaidi; Desy Eka Citra Dewi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This study develops a contextual Evaluation of Learning Quality and Output (EKOP) Model for Islamic educational institutions. The EKOP Model modifies the Kirkpatrick and CIPP approaches by emphasizing two main dimensions: the quality of the learning process (teacher input, methods, media, and environment) and learning output (improvement in students’ knowledge, attitudes, and skills) integrated with Islamic values. Using a library research method, this study analyzes the relevance, implementation, strengths, and challenges of applying the EKOP Model in madrasahs and Islamic schools. The results show that EKOP provides a more comprehensive evaluation framework and supports continuous improvement in line with the Islamic principles of hisbah and islah. However, the model requires adaptation to avoid neglecting the spiritual and ruhaniyah dimensions. This research is expected to contribute to improving the quality and accountability of Islamic education in Indonesia.